Successful Tocilizumab Therapy for Macrophage Activation Syndrome Associated with Adult-Onset Still’s Disease: A Case-Based Review - Eri Watanabe; Hitoshi Sugawara; Takeshi Yamashita; Akira Ishii; Aya Oda; Chihiro Terai (Case Reports in Medicine)
We report the case of a 71-year-old Japanese woman with adult-onset Still’s disease (AOSD) in whom macrophage activation syndrome (MAS) developed despite therapy with oral high-dose prednisolone and intravenous methylprednisolone pulse therapy twice. She was successfully treated with tocilizumab (TCZ). Soon afterward, her fever ceased and high levels of both ferritin and C-reactive protein levels decreased. Her course was complicated by disseminated intravascular coagulation, cytomegalovirus infection, and Pneumocystis jirovecii pneumonia. After these were resolved, AOSD-associated MAS was well controlled. She was discharged on hospital day 87. Although biologics such as TCZ are becoming established for the treatment of AOSD, there is no recommended therapy for AOSD-associated MAS. Several biologics have been tried for this complication, but their efficacy and safety remain controversial. We reviewed reported cases of AOSD-associated MAS successfully treated with various biologics. TCZ initiation after adequate nonselective immunosuppressive therapy, such as methylprednisolone pulse therapy or a prednisolone-based combination of immunosuppressants, can be an effective treatment for AOSD-associated MAS. On the other hand, biologics given after insufficient immunosuppressive therapy may cause MAS. A strategy combining adequate immunosuppression and a biologic could be safe if special attention is given to adverse events such as opportunistic infections or biologic-associated MAS.